Effect of cornsilk (Maydis stigma) addition in yeast bread: investigation on nutritional compositions, textural properties and sensory acceptability - Ng, S. H.; Wan Rosli, W. I. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
The proximate compositions, total dietary fibre (TDF) content, textural properties and sensory acceptability of yeast breads formulated with 0%, 2%, 4% and 6% of cornsilk powder (CSP) were studied. The protein, ash and TDF contents of yeast breads were increased in line with the CSP level added whereas moisture content was decreased. Yeast bread added with 6% CSP recorded the highest content of TDF (5.91%), protein (9.76%) and ash (1.03%) compared to other formulation of yeast breads containing lower percentage of CSP. Besides, texture profile analysis (TPA) reported that the firmness, gumminess and chewiness of yeast breads increased directly proportional to the level of CSP added mainly due to higher content of TDF and lower content of moisture. However, for the yeast bread added with 2%CSP, there were no significant differences compared with control yeast bread. Among all cornsilk-based yeast bread, formulation containing 2% CSP had the highest scores for all attributes including overall acceptance and there were no significant differences with control yeast bread. The present study indicated that the addition of 2% CSP could be an effective way to produce functional yeast bread without changing negatively its desirable textural and sensory acceptability.